Application of Oil-in-Water Cannabidiol Emulsion for the Treatment of Rheumatoid Arthritis - Jelínek, Petr; Roušarová, Jaroslava; Ryšánek, Pavel; Ježková, Martina; Havlůjová, Tereza; Pozniak, Jiří; Kozlík, Petr; Křížek, Tomáš; Kučera, Tomáš; Šíma, Martin; Slanař, Ondřej; Šoóš, Miroslav (Cannabis and cannabinoid research, 2024)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease with unknown cause. It mainly affects joints and, without proper treatment, negatively impacts their movement, causes painful deformities, and reduces the patients' quality of life. Current treatment options consist of various types of disease-modifying antirheumatic drugs (DMARDs), however 20-30% of patients are partially resistant to them. Therefore, development of new drugs is necessary. Possible option are compounds exhibiting their action via endocannabinoid system, which plays an important role in pain and inflammation modulation. One such compound - cannabidiol (CBD) has already been shown to attenuate synovitis in animal model of RA in in vivo studies. However, it has low bioavailability due to its low water solubility and lipophilicity. This issue can be addressed by preparation of a lipid containing formulation targeting lymphatic system, another route of absorption in the body. Materials and Methods: CBD-containing emulsion was prepared by high-shear homogenization and its droplet size distribution was analysed by optical microscopy. The relative oral bioavailability compared to oil solution as well as total availability of CBD were assessed in a cross-over study in rats and absorption of CBD via lymphatic system was observed. The effect of CBD on the animal model of RA was determined. Results: Compared to oil solution, the emulsion exhibited higher absolute oral bioavailability. Significant lymphatic transport of CBD was observed in all formulations and the concentrations in lymph were calculated. The therapeutic effect of CBD on RA was confirmed as an improvement in clinical symptoms as well as morphological signs of disease activity were observed during the study. Conclusion: In this work, we prepared a simple stable emulsion formulation, determined the pharmacokinetic parameters of CBD and calculated its absolute bioavailability in rats. Moreover, we successfully tested the pharmaceutical application of such a formulation and demonstrated the positive effect of CBD in an animal model of RA.
Keywords: emulsion; kvalita života; klinické křížové studie; voda; Rats; bolest; Water; Cannabidiol; Pain; in vivo study; rheumatoid arthritis; lymphatic absorption; Cross-Over Studies; Quality of Life; Animals; emulze; Arthritis, Rheumatoid; zvířata; bioavailability; cannabidiol; Administration, Oral; Emulsions; krysa rodu Rattus; kanabidiol; revmatoidní artritida; aplikace orální